Murder among friends : violation of philia in Greek tragedy - Belfiore, Elizabeth S., 1944- (Oxford University Press, 2000)
Modern scholars have followed Aristotle in noting the importance of philia (kinship or friendship) in Greek tragedy, especially the large number of plots in which kin harm or murder one another. More than half of the thirty-two extant tragedies focus on an act in which harm occurs or is about to occur among philoi who are blood kin. In contrast, Homeric epic tends to avoid the portrayal of harm to kin. It appears, then, that kin killing does not merely occur in what Aristotle calls the "best" Greek tragedies; rather, it is a characteristic of the genre as a whole. In Murder Among Friends, Elizabeth Belfiore supports this thesis with an in-depth examination of the crucial role of philia in Greek tragedy. Drawing on a wealth of evidence, she compares tragedy and epic, discusses the role of philia relationships within Greek literature and society, and analyses in detail the pattern of violation of philia in five plays: Aeschylus' Suppliants, Sophocles' Philoctetes and Ajax, and Euripides' Iphigenia in Tauris and Andromache. Appendixes further document instances of violation of philia in all the extant tragedies as well as in the lost plays of the fifth and fourth centuries BC.